Evaluación del proceso de transformación de camisetas posconsumo con base en poliéster para elaboración de aislante térmico en la ciudad de Bogotá D.C. (2022)
In this degree work, a thermal insulation design proposal is developed based on post-consumer polyester shirts in order to mitigate the environmental impacts caused by textile waste. To begin with, a bibliographic review was carried out with the objective of determining the amount of post-consumer waste that was being generated in the city of Bogotá, in addition, the information found allowed evaluating the environmental, economic and social impacts that these wastes were generating.